Noteworthy characteristics of the marketing decisions in service industry of emerging economies: Cases of Romania and Malaysia - Scarlat, Cezar; Kasim, Azilah (Universiti Utara Malaysia Press, 2007)
As a result of previous authors' research work and consulting experience, this paper presents some key aspects, specific to the relatively inexperienced management of the firms active in tourism and hospitality industry from emergent economies - such as that of Romania or Malaysia - and whether they are from small and medium size, or they are from recently privatized companies.Based on real cases, the sales elasticity curve is analyzed and a quantitative model is developed.In the domain of unit price - sales, the "Value Hysteresis" phenomenon is identified and defined. Non-linear dependence is identified as well, specific to the unbalanced markets (as far as supply-demand ratio) and extreme values of the elasticity coefficient are presented (such as E = 0 and E → - 8). Negative consequences of "automatic" marketing decisions based only on theoretical models are underlined - as their impact on clients' satisfaction and firm's profitability.Among the most important conclusions of the paper are: the key role of marketing information and research; importance of consumer loyalty; the growing role of the professional consulting services in management, mostly in tourism and hospitality industry from emerging economies.